Increasing soil water retention with native-sourced mulch improves seedling establishment in postmine Mediterranean sandy soils - Benigno, S.; Dixon, Kingsley; Stevens, J. (2013)
Seasonal drought and heavily impeded soils reduce restoration success in Mediterranean-type postmine soils, where up to 90% seedling mortality has been observed after 2 years. To alleviate these barriers, amendments were incorporated into the soil profile of a freshly mined sand quarry. Within the quarry, three 223 m2 replicate sites contained two substrate amendments: 12% v/v native-sourced mulch or gravel incorporated within the top 50 cm of the soil profile. Three remnant sites provided a “natural” reference system. Seeds of two autochthonous trees, Banksia attenuata (R.Br.) and B. menziesii (R.Br.) were sown across all treatments. Soil impedance, moisture, and seedling stomatal conductance were monitored for 2 years, at which point seedlings were excavated, and nutrient concentration, root morphology, and soil chemical properties were measured. Roots in all restoration treatments were restricted to the top 40 cm of the profile due to increases in soil impedance, regardless of amendment, compared to >70 cm in the natural system. Seedling mortality was greatest after the second summer in the control and inorganic amendment treatments, with stomatal conductance indicating severe drought stress. Survival in the organic treatment was 24–42% greater than the control, with higher soil moisture and stomatal conductance rates 2.5 times that of the control. The increased soil water retention by a native-sourced mulch was shown to improve postmine restoration success for these native trees.